Genomic Organization and Comparative Phylogenic Analysis of NBS-LRR Resistance Gene Family in Solanum pimpinellifolium and Arabidopsis thaliana. (March 2020) - Wei, Huawei; Liu, Jia; Guo, Qinwei; Pan, Luzhao; Chai, Songlin; Cheng, Yuan; Ruan, Meiying; Ye, Qingjing; Wang, Rongqing; Yao, Zhuping; Zhou, Guozhi; Wan, Hongjian
NBS-LRR (nucleotide-binding site and leucine-rich repeat) is one of the largest resistance gene families in plants. The completion of the genome sequencing of wild tomato Solanum pimpinellifolium provided an opportunity to conduct a comprehensive analysis of the NBS-LRR gene superfamily at the genome-wide level. In this study, gene identification, chromosome mapping, and phylogenetic analysis of the NBS-LRR gene family were analyzed using the bioinformatics methods. The results revealed 245 NBS-LRRs in total, similar to that in the cultivated tomato. These genes are unevenly distributed on 12 chromosomes, and ~59.6% of them form gene clusters, most of which are tandem duplications. Phylogenetic analysis divided the NBS-LRRs into 2 subfamilies (CNL-coiled-coil NBS-LRR and TNL-TIR NBS-LRR), and the expansion of the CNL subfamily was more extensive than the TNL subfamily. Novel conserved structures were identified through conserved motif analysis between the CNL and TNL subfamilies. Compared with the NBS-LRR sequences from the model plant Arabidopsis thaliana, wide genetic variation occurred after the divergence of S. pimpinellifolium and A thaliana . Species-specific expansion was also found in the CNL subfamily in S. pimpinellifolium . The results of this study provide the basis for the deeper analysis of NBS-LRR resistance genes and contribute to mapping and isolation of candidate resistance genes in S. pimpinellifolium .